Penetapan Wali Adhol Dalam Perkawinan Masyarakat Muslim Binjai - Hamdi, Abdul Ridho; Jamil, Muhammad; Siregar, Ramadhan Syahmedi (Lembaga Dakwah dan Pembangunan Masyarakat Universitas Cokroaminoto Yogyakarta (LDPM UCY), 2023)
This study wanted to find out the procedural in the application for wali adhol and the number of cases at the Binjai Religious Court. Then the cause of the application for guardian adhol in the people of Binjai City to the Binjai Religious Court and the peaceful effort and the basis for determining the panel of judges at the Binjai Religious Court on the appointment of guardian judges in Muslim community marriages in Binjai City whose guardians are adhol. The type of thesis research is qualitative, the type of research is yuridis sosiologis, namely the type of social research research. The primary source of research is the decision of the Binjai Religious Court in determining the guardian adhol from 2011-2021. Data collection techniques by means of observation, interviews, document studies and photos. Based on the results of the study that the Guidelines and Administrative Duties of the Religious Courts related to the application for wali adhol which was requested by the prospective bride to the Binjai Religious Court, namely registering the case and paying the down-payment of the case; the application can be submitted cumulatively, namely the determination of the guardian adhol as well as a marriage permit and the appointment of a guardian judge; The head of the Religious Court determines the panel of judges in charge.